Graphene in Light: Design, Synthesis and Applications of Photo-active Graphene and Graphene-Like Materials - Wang, Hang-Xing; Wang, Qiang; Zhou, Kai-Ge; Zhang, Hao-Li (Small (Weinheim an der Bergstrasse, Germany), 2013)
Graphene functionalized with photo‐active units has become one of the most exciting topics of research in the last few years, which remarkably sustains and expands the graphene boom. The rise of photo‐active graphene in photonics and optoelectronics is evidenced by a spate of recent reports on topics ranging from photodetectors, photovoltaics, and optoelectronics to photocatalysis. For these applications, the fabrication of photo‐active graphene through appropriate chemical functionalization strategies is essential as pristine graphene has zero bandgap and only weak absorption of photons. Written from the chemists' point of view, up‐to‐date chemical functionalization of graphene with various small organic molecules, conjugated polymers, rare‐earth components, and inorganic semiconductors is reviewed. Particular attention is paid to the development of graphene functionalized with light‐harvesting moieties, including materials synthesis, characterization, energy/charge‐transfer processes, and applications in photovoltaics. Challenges currently faced by researchers and future perspectives in this field are also discussed. Combining the unique electrical and mechanic properties of graphene with the excellent optical properties of various photo‐active moieties, functionalized graphene has true potential for photodetectors, optoelectronics, photovoltaics, and photocatalysis.